Synergistic doping with Ag, CdO, and ZnO to overcome electron-hole recombination in TiO2 photocatalysis for effective water photo splitting reaction - Erfan, Nehal A.; Mahmoud, Mohamed S.; Kim, Hak Yong; Barakat, Nasser A. M. (Frontiers in Chemistry, 2023)
This manuscript is dedicated to a comprehensive exploration of the multifaceted challenge of fast electron-hole recombination in titanium dioxide photocatalysis, with a primary focus on its critical role in advancing the field of water photo splitting. To address this challenge, three prominent approaches—Schottky barriers, Z-scheme systems, and type II heterojunctions—were rigorously investigated for their potential to ameliorate TiO2’s photocatalytic performance toward water photo splitting. Three distinct dopants—silver, cadmium oxide, and zinc oxide—were strategically employed. This research also delved into the dynamic interplay between these dopants, analyzing the synergetic effects that arise from binary and tertiary doping configurations. The results concluded that incorporation of Ag, CdO, and ZnO dopants effectively countered the fast electron-hole recombination problem in TiO2 NPs. Ag emerged as a critical contributor at higher temperatures, significantly enhancing photocatalytic performance. The photocatalytic system exhibited a departure from Arrhenius behavior, with an optimal temperature of 40°C. Binary doping systems, particularly those combining CdO and ZnO, demonstrated exceptional photocatalytic activity at lower temperatures. However, the ternary doping configuration involving Ag, CdO, and ZnO proved to be the most promising, surpassing many functional materials. In sum, this study offers valuable insights into how Schottky barriers, Z-scheme systems, and type II heterojunctions, in conjunction with specific dopants, can overcome the electron-hole recombination challenge in TiO2-based photocatalysis. The results underscore the potential of the proposed ternary doping system to revolutionize photocatalytic water splitting for efficient green hydrogen production, significantly advancing the field’s understanding and potential for sustainable energy applications.